Dural Arteriovenous Fistula at the Anterior Condylar Confluence - Miyachi, S. (Centauro S.r.l., 2008)
We reviewed the records of eight patients with a dural arteriovenous fistula (DAVF) close to the hypoglossal canal and determined the angioarchitecture of the clinical entity at the anterior condylar confluence. Eight patients with DAVF received endovascular treatment at our institute over the past five years. Imaging with selective three-dimensional angiography and thin-slice computed tomography were used to identify the fistula and evaluate the drainage pattern. Based on the angiographic findings, the ascending pharyngeal artery was the main feeder in all cases, and the occipital, middle meningeal, posterior auricular, and posterior meningeal arteries also supplied the DAVF to varying degrees. Contralateral contribution was found in five patients. The main drainage route was the external vertebral plexus via the lateral condylar veins in four patients, the inferior petrosal sinus in three patients, and the internal jugular vein via the connecting emissary veins in one patient. Selective angiography identified the shunt point at the anterior condylar confluence close to the anterior condylar vein. Shunt occlusion with transvenous coil packing was performed in all cases; transarterial feeder embolization was also used in three patients. Two patients treated with tight packing of the anterior condylar vein developed temporary or prolonged hypoglossal palsy. Based on our results, the main confluence of the shunt is located at the anterior condylar confluence connecting the anterior condylar vein and multiple channels leading to the extracranial venous systems. To avoid postoperative nerve palsy, the side of the anterior condylar vein in the hypoglossal canal should not be densely packed with coils. Evaluating the angioarchitecture using the selective three-dimensional angiography and tomographic imaging greatly helps to determine the target and strategy of endovascular treatment for these DAVF.